The Influence of Emotional Intelligence and Organizational Citizenship Behavior on The Performance of Employees of PT. Trisamudra Ambon - Saleh Tutupoho; Pieter N. R. Rehatta; Defvita Sari Salmon (PT ARRUS Intelektual Indonesia, 2024)
The title of this study is the Effect of Emotional Intelligence and Organizational Citizenship Behavior on employee performance at PT. Trisamudra Ambon. Respondents in the study were 55 consisting of employees of PT. Trisamudra Ambon. The data collection methods used in this study were questionnaires, interviews, and in analyzing the data using multiple linear regression analysis techniques, classical assumption test. Normality test Multicolonearity Test, Heteroscedasticity Test, Coefficient of Determination Test (R2), and Partial Test (t test). Based on the hypothesis testing, it was found that the t value of Emotional Intelligence was 2.491 > t table 1.671, while the significance value was 0.016. These results can be interpreted as a significance value smaller than 0.05 which indicates that Emotional Intelligence has a significant effect on Employee Performance while the t-value of Organizational Citizenship Behavior is 3,410 > ttable 1,671 while the significance value is 0,001. These results can be interpreted that the significance value is less than 0.05, this means that OCB has a significant effect on employee performance Thus, the hypothesis in this study which states that Emotional Intelligence and Organizational Citizenship Behavior has a positive and significant effect on employee performance